2017
DOI: 10.3390/ijms18081674
|View full text |Cite
|
Sign up to set email alerts
|

Strategies towards Improved Feed Efficiency in Pigs Comprise Molecular Shifts in Hepatic Lipid and Carbohydrate Metabolism

Abstract: Due to the central role of liver tissue in partitioning and metabolizing of nutrients, molecular liver-specific alterations are of considerable interest to characterize an efficient conversion and usage of feed in livestock. To deduce tissue-specific and systemic effects on nutrient metabolism and feed efficiency (FE) twenty-four animals with extreme phenotypes regarding residual feed intake (RFI) were analyzed. Transcriptome and fatty acid profiles of liver tissue were complemented with measurements on blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 51 publications
3
33
1
Order By: Relevance
“…They also reported reduced hepatic usage of fatty acid in high FE animals with a molecular alteration in lipid metabolism. A complementary analysis pointed out increased circulating triglycerides accompanied by a lower concentration of saturated and polyunsaturated fatty acids in the liver of high FE pigs 14 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…They also reported reduced hepatic usage of fatty acid in high FE animals with a molecular alteration in lipid metabolism. A complementary analysis pointed out increased circulating triglycerides accompanied by a lower concentration of saturated and polyunsaturated fatty acids in the liver of high FE pigs 14 .…”
Section: Discussionmentioning
confidence: 98%
“…Studies reported the relationship of B6 in tryptophan metabolism of weanling piglets but were unable to detect an effect on the oxidation of the tryptophan pathway and suggested that B6 may stimulate another pathway in tryptophan metabolism 29 . Metabolic shifts in lipid and carbohydrate utilization in high FE animals were reported 14 . They also reported reduced hepatic usage of fatty acid in high FE animals with a molecular alteration in lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…KAT2B was involved with thyroid hormone signaling pathway. The systemic effects mediated by thyroid hormones induces metabolic shifts characterized by increased lipolysis and gluconeogenesis, affecting feed efficiency in pigs (Reyer et al, 2017a). MAPKs regulates (either stimulating or inhibiting) the catalytic activity, and specificity, of kinases and phosphatases that are involved in the metabolism of phosphatidylinositols (PI) and inositol phosphates (IP), thereby exert regulatory actions on PIand/or IP-dependent signaling pathways (Caldwell et al, 2006).…”
Section: Mtor and Mapk: Key Signaling Pathways In Durocmentioning
confidence: 99%
“…Recently, a global transcriptome analysis in the duodenum of laying ducks showed that genes involved in lipid metabolism play an important role in regulating feed efficiency [20]. Moreover, a previous study suggested that lipid metabolism in the liver and lipid absorption in the intestine were two important factors affecting feed efficiency traits [10]. Lipids are a vital nutrient widely utilized in almost all tissues of the body, and they play a key role in animal growth and development [21].…”
Section: Discussionmentioning
confidence: 99%
“…triglyceride and cholesterol) in the abdominal fat tissue using RNA-Seq [9]. The liver and duodenum both play vital roles in the regulation of lipid absorption, metabolism, and appetite regulation [10,11]. The liver is a key organ in lipid processing, packaging, and redistribution [12].…”
Section: Introductionmentioning
confidence: 99%